L’assurance et la réassurance : une industrie en mutation - Parizeau, Robert (Assurances, 1990)
In his article, Mr. Robert Parizeau, President and Chief Executive Officer of Sodarcan inc., presents a timely overview of the major changes experienced by financial institutions over the past decade. These changes were brought on both by the institutions themselves, through mergers and reorganizations, and by legislators who have undertaken to revise the laws and regulations governing this sector. ln his conclusion, Mr. Parizeau briefly examines specific recent laws and legislative reforms which will profoundly affect our industry.